Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Lexington Books, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Sliding Back the Screens: Civil Society and the Erosion of Bureaucratic Control of Television in Japan - Hirano, Chalinee (Television, Regulation and Civil Society in Asia, 2002)
Japan in the 1990s differs vastly from what it had been two or three decades earlier. The Japanese state has undergone such a fundamental change that it has been described as a ‘regime shift’ (Pempel 1998). Although the longterm ruling conservative Liberal Democratic Party (LDP) has returned to power after its defeat in 1993, it no longer has an absolute majority in the Cabinet. Surrounded by numerous scandals and corruption charges, both the government and bureaucracy have undergone major reforms to increase transparency and reduce bureaucratic influence over the policy-making process. The Japanese Diet has, for example, passed the Information Disclosure Law to increase openness in the administration. Economic policies have also been transformed to cope with the malaise characterised by continuing problems of bad loans in the financial sector, rising unemployment and declining manufacturing productivity.
Num Pages: 9
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Japon (corpus analysé); _Nettoyé

Out of Reach: Television, the Public Sphere and Civil Society in the Philippines - Santos, Josefina M. C. (Television, Regulation and Civil Society in Asia, 2002)
In the uprising of 16-20 January 2001, which ousted former Philippine President Joseph Estrada from power, two forces stood out as pivotal: television (specifically the coverage of the impeachment trial which was the centre of public attention) and civil society (which was instrumental in the uprising itself). In this chapter I argue that notwithstanding the central importance of television in this most recent national political change, the regulation of the sector and its long-term associations with crony capitalism have established barriers to civil society finding its voice on television.
Num Pages: 1
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Philippines (corpus analysé); Philippines (lieu de production du savoir); _Nettoyé

Civic or Civil Contingencies?: Regulating Television and Society in Singapore - Birch, David; Phillips, Marianne (Television, Regulation and Civil Society in Asia, 2002)
Singapore has changed dramatically in the last forty years, moving in the 1960s and 1970s from domestic import substitution to low-cost exportoriented goods. Then in the 1980s developing a regional financial and business hub and now increasingly positioning itself as an exporter of capital and expertise (Courtenay 1995: 90). With exceptionally high economic growth rates most years, a GNP per capita of US$6,000 more than Australia and three times Australia’s annual average growth, Singapore has attracted a high percentage of foreign direct investment. Despite exhibiting similar advantages to Australia in terms of a well-educated workforce, competitive pricing, developed transport and telecommunications and citizens from culturally diverse business, family and personal networks throughout the region, Singapore’s media and resultant civil and civic development has not been as progressive and liberal as Australia’s and indeed has not kept pace. So it would appear that state existence, security and prosperity as desired ends for Singapore do not necessarily rely on an equal strengthening of the public sphere, or at least this is not evident to date.
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé

Prime Time Soap Operas on Indian Television - Munshi, Shoma (Routledge India, 2020)
This book examines the phenomenon of prime time soap operas on Indian television. An anthropological insight into social issues and practices of contemporary India through the television, this volume analyzes the production of soaps within India’s cultural fabric. It deconstructs themes and issues surrounding the "everyday" and the "middle class" through the fiction of the "popular". In its second edition, this still remains the only book to examine prime time soap operas on Indian television. Without in any way changing the central arguments of the first edition, it adds an essential introductory chapter tracking the tectonic shifts in the Indian "mediascape" over the past decade – including how the explosion of regional language channels and an era of multiple screens have changed soap viewing forever. Meticulously researched and persuasively argued, the book traces how prime time soaps in India still grab the maximum eyeballs and remain the biggest earners for TV channels. The book will be of interest to students of anthropology and sociology, media and cultural studies, visual culture studies, gender and family studies, and also Asian studies in general. It is also an important resource for media producers, both in content production and television channels, as well as for the general reader.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Koweït (lieu de production du savoir); _Nettoyé

Television Regulation and Media Policy in China - Chin, Yik-Chan (Routledge, 2016)
Since the late 1990s, there has been a crucial and substantial transformation in China’s television system involving institutional, structural and regulatory changes. Unravelling the implications of these changes is vital for understanding the politics of Chinese media policy-making and regulation, and thus a comprehensive study of this history has never been more essential. This book studies the transformation of the policy and regulation of the Chinese television sector within a national political and economic context from 1996 to the present day. Taking a historical and sociological approach, it engages in the theoretical debates over the nature of the transformation of media in the authoritarian Chinese state; the implications of the ruling party’s political legitimacy and China’s central-local conflicts upon television policy-making and market structure; and the nature of the media modernisation process in a developing country. Its case studies include broadcasting systems in Shanghai and Guangdong, which demonstrate that varied polices and development strategies have been adopted by television stations, reflecting different local circumstances and needs. Arguing that rather than being a homogenous entity, China has demonstrated substantial local diversity and complex interactions between local, national and global media, this book will be of interest to students and scholars of Chinese media, politics and policy, and international communications.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Shifts in Korean Television Music Programmes: Democratization, Transnationalization, Digitalization - Jung, Sun (Television Histories in Asia: Issues and Contexts, 2015)
Korea was the fifteenth country in the world to start television broadcasting when it first launched in Seoul in 1956. Since then, the structure, content and policies concerning Korean television have continuously transformed, due largely to changing contextual circumstances such as wide-ranging socio-political democratization and the rise of the neoliberal global economic system and digital technologies. Up until the 1980s, the oligopolistic structure of the two public broadcasting networks – Korean Broadcasting System (KBS) and Munhwa Broadcasting Corporation (MBC) – dominated the broadcasting market. However the landscape has dramatically changed since the early 1990s, with 11 newly launched commercial terrestrial broadcasting channels (including Seoul Broadcasting System (SBS) in December 1991) and 153 cable channels when the multichannel television era began (Jin 2005 : 1). A digital satellite television system called Skylife was launched in March 2002, and airs 176 channels at the time of writing. Such changes stem from the shift in the domestic political climate where liberalization and privatization were promoted in assertively practiced neoliberal reform movement in the early 1980s, as well as changes in the global cultural industry environments based largely on globalization and the development of digital technologies. This chapter explores democratization, transnationalization and digitalization, three active factors within Korean television broadcasting by analysing changes and shifts in popular music programmes.
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Watching Television in Bhutan - Avieson, Bunty (Television Histories in Asia: Issues and Contexts, 2015)
The kingdom of Bhutan drew the international spotlight in 1999 when it became the last nation on earth to introduce broadcast television. It was a deliberate and strategic move by a country that for centuries had chosen to isolate itself from the rest of the world, turning inward to nurture its own culture. The small Himalayan country, whose population in 2013 was estimated at just 733,000, 1 sits uneasily between two feisty behemoths – China and India – each with over a billion people and an ongoing history of border disputes. Bhutan has long been wary of being swamped, either politically or culturally, by these larger neighbours, as well as the world beyond (Penjore 2004 ).
Num Pages: 16
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Bhoutan (corpus analysé); _Nettoyé

Trust and Television in Globalizing India - McMillin, Divya (Television Histories in Asia: Issues and Contexts, 2015)
Writing a history of Indian television immediately begs the question, how do we want it read? Exhaustive chronological treatments anchor the field (Kumar 2000 ), ideological examinations reveal a Hindu-centric nation with serious consequences for religious and gender minorities (Rajagopal 1996 ; Mitra 1993 ; Van der Veer 1997 ), development analyses demonstrate the failures of a socialist state (F ü risch and Shrikhande 2007 ), and audience studies reveal complex negotiations among multiple identity positions (Mankekar 1999 ). These critical approaches to the study of television in India rightly expose power differentials that facilitate, through the centuries, the inequities of interwoven structures of imperialism, colonialism, casteism, and capitalist patriarchy. Most importantly, they highlight the chronic condition of distrust in postcolonial societies, making it highly challenging to legitimize profi table connections to global circuits as they modernize under the very conditions that once constrained them.
Num Pages: 20
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Scale and Place-Identity in the PRC: Provincial, National and Global Influences from 1958 to 2013 - Sun, Wanning; Gorfinkel, Lauren (Television Histories in Asia: Issues and Contexts, 2015)
One may argue that Chinese television has already received more than its fair share of attention in the study of Chinese media. As compared with radio and cinema, which developed in the socialist era (1949-78), television has been seen as the dominant medium in the decades of marketization and economic reforms since the late 1970s (Zhu and Berry 2008 ). Television has been studied as a metonym for the ongoing tension and complicity between the Chinese state and the market (e.g., Zhao 1998 ; 2008a) and as a metaphor for the contradictions between a legacy of socialist rhetoric and ethos and a neoliberal market agenda. It is precisely these contradictions that make up what is often referred to as the ‘Chinese characteristics’ (Zhao 2008a; Sun and Zhao 2009 ) of China’s television culture.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Sange ThakunBangla News Channels and Media-Citizenry - Gupta, Nilanjana (Channeling Cultures: Television Studies from India, 2014)
With special reference to the current scenario in West Bengal, this chapter argues that the rise and popularity of Bangla news channels like Star Ananda, 24 Ghanta, Kolkata TV, and Tara News have resulted in the emergence of a vernacular style of news broadcasting which is quite distinct from that of global or national news media. One major point in this chapter is how the vernacular news channels encourage particular forms of address — the emotional, the intimate and the melodramatic — and how close-ups and sound bites create particular kinds of telegenic political leaders who can use these formal characteristics to their advantage. This chapter explores the ways in which a distinctive kind of vernacular is reconfiguring the nature of political participation itself and hence the notion of citizenship and perhaps even the nature and functioning of the nation-state in India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

From Quinceañera to Miss XV: Coming of Age in Mexican Screen Melodrama - Rios, Sofia (Children, Youth, and International Television, 2022)
This chapter historicises and contextualises the evolution, production, and development of key Mexican screen melodramas over fifty-two years to understand and mediate Mexico’s ambivalence around socioeconomic background, ranother. Perhaps if Televisa had allowed its various ace and religion, gender and worth, family and duty. The chapter demonstrates the importance of localised scholarly inquiry into Mexican audiovisual media that considers not only narrative discourses, content and textual analyses, but also industrial records and practices, marketing campaigns and press releases, archival research and interviews, multimedia synergy, and comparative analysis. For some time, research on Mexican melodrama has had a strong social focus, with several writings about audience engagement, but it is imperative to have more close readings of the texts themselves to understand their cultural context and industrial histories. This research exposes societal changes within Mexico by utilising one of its most omnipresent forms of popular culture and provides a deeper understanding of Mexico’s primary media productions through the use of genre and remake theory. The representations of young women yield a multitude of tensions and ambiguities placed upon Mexican women, which reveal volumes about wider sociocultural expectations.
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; Australie (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Globalization and Television: A Study of the Indian Experience, 1990-2010 - Narayan, Sunetra Sen (Oxford University Press, 2013)
This study explores the globalization and liberalization that has occurred in Indian television over the two decades starting from 1990.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Digital Terrestrial Television Broadcasting (DTTB) in Botswana: Prospects and Challenges - Mosanako, Seamogano; Lesitaokana, William O. (Television in Africa in the digital age, 2021)
The year 2015 was set by the International Telecommunication Union (ITU) for most of its member states globally to switch from analogue to digital terrestrial broadcasting. Digital television broadcasting is generally implied as transmission of broadcast content signals in the form of binary data, speciﬁcally 0 s and 1 s. Digitisation of television merges broadcasting, computing and telecommunications to transform both the way television content is made and consumers interact with content (Chalaby and Segell 1999). Referring to digital content, Flew (2004) suggested that digitisation of media and communication content grows “informatisation” of society.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Botswana (corpus analysé); Botswana (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Digitization of Television in Kenya: Changing Trends in Content and Consumption - Murunga, Protus; Diang'a, Rachael (Television in Africa in the Digital Age, 2021)
The purpose of this chapter is to examine how the digitization of television has impacted the architecture of television content generation, dissemination consumption in Kenya. Its key motivation is to answer two main questions: How has the digitization shift in Kenya’s television impacted the trends in production, dissemination, reception and consumption of television content; what is the effect of digitization on viewer satisfaction; and how has this shift transformed the role of television medium in the country? The chapter, therefore, answers these questions focusing on the television channels under study, namely, Citizen TV, Kenya Broadcasting Corporation (KBC) and Nation TV (NTV).
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Kenya (corpus analysé); Kenya (lieu de production du savoir); _Nettoyé

Exodus, Access and Inequalities: The Impact of Digital Migration in the Least Developed Countries of Africa - Motsaathebe, Gilbert; Chiumbu, Sarah H. (Television in Africa in the Digital Age, 2021)
There has been a hype regarding the beneﬁts of digital migration, which refers to switchover from analogue to digital broadcasting. Commonly referred to as digital migration, the switchover emanates from a decision made at the International Telecommunications Union (ITU) in 2006 to release a valuable spectrum, which can be used for other services. Other beneﬁts of digital TV include good sound and picture quality and availability of more channels giving viewers more choice. It has also been said that digital broadcasting will save the broadcasting stations’ cost, as transmitting content via digital platforms is less costly than transmitting via the analogue platform (Muthomi 2012). This implies that media houses can capitalise on this migration as a competitive advantage. Countries across the world have been undergoing this necessary switchover from analogue to digital platforms, with varying degree of success. While the merits of digital television are clear, it is not clear how this digitisation will realistically help in bridging habitual inequalities in developing countries.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (lieu de production du savoir); _Nettoyé

Digital Disruption in South African Television News - Stos, Susan (Television in Africa in the Digital Age, 2021)
The term digital “disruption” conjures up negative connotations, with implications of disturbance, interference or interruption. Certainly, virtually every aspect of life has been affected by digitisation, but it has been pointed out that it is detrimental “only for those who chose to ignore it or try to ﬁght it” (“Digital Disruption: What Is It?” 2016, para 2). One case in point is the American company Kodak. Where it once dominated the ﬁlm and camera market for most of the twentieth century, the company recently ﬁled for bankruptcy. Kodak’s mistake was continually opposing the digitisation of the industry and failing to read the writing on the wall (“Digital Disruption: What Is It?” 2016). Digitisation is as much a reality of life in the newsroom as it is in the boardroom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Understanding Netflix's Foray into Original Productions in South Africa: A "Jet Plane" and "Helicopter" View - Chambwera, Collen (Television in Africa in the Digital Age, 2021)
Until recently, the South African television industry was dominated by the South African Broadcasting Corporation (SABC), etv, and Multichoice. The SABC and etv are free to air while Multichoice provides a satellite subscription service through its DSTV bouquet. This status quo was broken with the emergence of subscription video on demand (SVOD). While Multichoice launched its SVOD service, Showmax, in 2015, greater disruption happened in January 2016 when the current most successful global company in SVOD, Netﬂix, simultaneously launched in 130 countries including South Africa. The coming of Netﬂix to South Africa was reportedly greeted by excitement as viewers embraced choice of access to premium television entertainment. Considering that prior to this development, Multichoice had had a near monopoly in provision of premium television content through its DSTV and Showmax, the reported excitement came as no surprise.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Chinese Television and Soft Power Communication in Australia - Li, Mei (Anthem Press, 2019)
Chinese Television and Soft Power Communication in Australia discusses China’s soft power communication approach and investigates information handling between China and its targeted audiences in the eyes of key influencers – intermediate elites (public diplomacy policy elites in particular) in China and Australia. It explores CGTN (with staff from several professional cultures) and conducts a systemic test of how successful/unsuccessful China’s soft power message projection is in terms of congruence between projected and received frames as a pivotal factor of its power status. The analysis is based on a case study of frames in the messaging on Chinese international TV about China’s Belt and Road Initiative and in the minds of Australian public diplomacy policy elites. The question raised is whether and how Australia is listening.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Australie (corpus analysé); Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Producing Domestic Abuse in Pakistani Television: Between Commerce, Ratings and Social Responsibility - Cheema, Munira (Television for Women, 2016)
Before the liberalisation of television in 2000, Pakistan had one terrestrial channel.The Pakistan Television Corporation (commonly known as PTV) had been the statebroadcaster since 1964 and thus PTV content reflected the policies of differentgovernments. Liberal governments relaxed control over gender on screen – womencould be seen without dupatta – while religiously inclined governments brought intheir own agendas with restrictions on appearance of women, such as the dupattapolicy (see, for example, Ali, 1986; Suleman, 1990; Kothari, 2005; Nasir, 2012).1 In2002, the Independent Media Corporation launched its channel Geo News fromPakistan, followed by other networks, marking the formal launch of the policy ofliberalisation of media on television. Presently, five media groups have control of thePakistani media industry, including electronic and print media. These are Inde-pendent Media Corporation, Pakistan Herald Publications, ARY Group, WaqtGroup and Lakson Group (see for example Proffitt and Rasul, 2013). The broad-casting industry in Pakistan follows an advertiser-driven model that is run through asystem of ratings. At the time of the fieldwork reported here (October-April 2011),Media Logic and Gallup were the two operators that determined the popular tastesof consumers through ratings.2
Num Pages: 20
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); _Nettoyé

Defining the Nation?: Lebanese Television and Political Elites (1990–2005) - Nötzold, Katharina (Frank & Timme, 2013)
Katharina Nötzold explores whether and how mass media can contribute to nation-building after civil war. Drawing on the example of Lebanon’s audiovisual media organisations, which are mostly privately owned by politicians, she demonstrates how political elites use television to transmit their visions of post-war society. Lebanon’s nation-building process from 1990 to 2005 was characterized by Syrian dominance over political life. From an extensive content analysis of Lebanese news and interviews with analysts, journalists and managers from all Lebanese TV stations, it emerges that political information on television focused more on divisive experiences than cohesive ones. This has underpinned continued sectarianism in Lebanon, in the media as in society at large, and has impeded nation-building. Biographische Informationen Katharina Nötzold is a political scientist and RCUK Research Fellow at the University of Westminster's Arab Media Centre, and she completed her PhD in Media and Communications at the University of Erfurt, Germany. She lived in Beirut and Amman and worked previously for the Center for International Peace Operations, Berlin. She is editor of Westminster Papers in Communication and Culture and author of articles on Arab media and media representations of migrants and Islam. Reihe Medien und politische Kommunikation – Naher Osten und islamische Welt - Band 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Allemagne (lieu de production du savoir); Liban (corpus analysé); _Nettoyé

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Watching Si Doel: Television, Language and Identity in Contemporary Indonesia - Loven, Klarijn (BRILL, 2008)
While television in today's world increasingly displays a global character, national television systems are still firmly rooted in a specific locality. But in what ways does this locality actually shape the content and performance of national television? What is the significance of local cultures and local languages in these processes of mediation? And how do the local, the national, and the global intersect in discourses of and discourse on television? Taking a critical discourse analysis perspective, Watching Si Doel investigates these and related questions in the context of contemporary Indonesia. Starting from the nationwide popularity of the local television serial Si Doel Anak Sekolahan ("Educated Doel"), it examines the various ways in which the national government, Indonesian television producers, and local audiences shape, interpret, and struggle over the meaning of the phrase 'national television'. In doing so, the book explores what Indonesian television at the turn of the century sounds and looks like–and, significantly, ought to sound and look like–according to those who create and control television and those who watch and interpret it. While providing insight into the production, nature, and reception of television discourse in general, this book particularly seeks to clarify the relationship between television, language, and power in late New Order and post-Soeharto Indonesia.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; Indonésie (corpus analysé); Pays-Bas (lieu de production du savoir); _Nettoyé

Telly-Guillotined: How Television Changed India - Shah, Amrita (SAGE Publications India Pvt, Ltd., 2019)
Fist-fights in television studios, dwindling media autonomy, sensationalism, fake news, religious hate, abusive trolls, political spin ... How did we get here? Three decades ago, before economic liberalization, came the expansion and privatization of Indian television. Technological innovation and easing of government controls offered the prospect of journalistic independence, artistic creativity and an empowered citizenry. This was rendered illusory by runaway growth and untrammelled commercialization. In that thwarted promise of the late 20th century lie the seeds of Indian democracy's current crisis. Telly-Guillotined: How Television Changed India tells the story of how technology was usurped, first by propagandists, then by the market. Going behind the scenes of the world′s greatest media explosion, this book describes the impact of consumerism on the newsroom, the shaping of a new cultural politics and the rise of a new politics of seduction. In a landscape of technological innovation, blurred boundaries and sensory overload, Amrita Shah paints a picture of the Fourth Estate′s challenging future.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Inde (lieu de production du savoir); _Nettoyé

Muy buenas noches: Mexico, Television, and the Cold War - Gonzalez de Bustamante, Celeste (Nebraska Paperback, 2013)
By the end of the twentieth century, Mexican multimedia conglomerate Televisa stood as one of the most powerful media companies in the world. Most scholars have concluded that the company’s success was owed in large part to its executives who walked in lockstep with the government and the Partido Revolucionario Institucional (PRI), which ruled for seventy-one years. At the same time, government decisions regulating communications infrastructure aided the development of the television industry. In one of the first books to be published in English on Mexican television, Celeste González de Bustamante argues that despite the cozy relationship between media moguls and the PRI, these connections should not be viewed as static and without friction. Through an examination of early television news programs, this book reveals the tensions that existed between what the PRI and government officials wanted to be reported and what was actually reported and how. Further, despite the increasing influence of television on society, viewers did not always accept or agree with what they saw on the air. Television news programming played an integral role in creating a sense of lo mexicano (that which is Mexican) at a time of tremendous political, social, and cultural change. At its core the book grapples with questions about the limits of cultural hegemony at the height of the PRI and the cold war.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

A telenovela brasileira: do nacionalismo à exportação - Santos, Lidia (Caravelle. Cahiers du monde hispanique et luso-brésilien, 2000)
Rentable produit d'exportation diffusé dans 128 pays, le feuilleton télévisé brésilien fait partie du quotidien de la population depuis une trentaine d'années. Si une grande part de son succès repose sur l'exploitation de « la culture des sentiments », dans sa version la plus moderne, il sait aussi plonger au cœur de la réalité comme l'a démontré entre autres avec brio « Le roi du troupeau » (1986) qui mettait en scène le conflit entre les sans-terre et les grands propriétaires terriens.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)